Pelatihan Hidroponik kepada Warga di Kampung Tempe Ciomas, Desa Ciomas Rahayu Guna Meningkatkan Ketahanan Pangan Keluarga - Wulandari, Yasinta Ratna Esti; Hartanti, Anastasia Tatik; Soelasih, Yasintha; Chow, Aozora Valentinus; Theja, Serafina; Johan, Philip Dave (Institute for Research and Community Services, 2024)
Hydroponics can be an additional learning tool for the community to achieve sustainable development goals. With the community service activities for the residents of Kampung Tempe Ciomas carried out by a team of lecturers from the Faculty of Biotechnology and Faculty of Economics and Business together with students, residents can gain additional knowledge and skills in planting hydroponically, where the harvest can then be used for consumption or as a production result with profitable aspect. The training was carried out offline, including the theory and practice of hydroponic techniques which are expected to maximize the use of existing hydroponic facilities. The monitoring results were carried out after planting for 45 days using lettuce and bok choy plants with parameters of plant height, number of leaves, root length, and wet weight of the plant. From the harvested results, Group 2 obtained the highest wet weight for lettuce at 141.14 grams, while Group 3 obtained the highest wet weight for bok choy at 143 grams. The evaluation and questionnaire for the activity were conducted using Microsoft Forms. The evaluation showed positive results in assessing the residents knowledge and understanding of hydroponic practices, the quality of tools and materials, as well as their interest in continuing hydroponic practices. Overall, the workshop activities can be considered to have gone quite well and adequately.